PERAN GURU BK DALAM MENGATASI DAMPAK PERUBAHAN SOSIAL DAN TEKANAN MEDIA SOSIAL TERHADAP KESEHATAN MENTAL REMAJA - Dwi Rahmawati , Aulia; Rafidah Nuraniyah , Andi; Siti Shalma, Elsa; Fauzia, Silvi; Nurkholis, Nurkholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Rapid social changes due to the development of digital technology, particularly the use of social media, have a significant impact on adolescent mental health. Intense interaction in the digital world can lead to various psychological problems such as anxiety, stress, decreased self-esteem, difficulty managing emotions, and obstacles in developing a self-identity. In the field of education, Guidance and Counseling (BK) teachers play a crucial role in helping adolescents cope with these psychosocial pressures. This study aims to evaluate the role of BK teachers in addressing the impact of social change and social media pressures on adolescent mental health. This study used a literature review method by analyzing various domestic and international journal articles, academic books, and reports from official institutions related to the topics of adolescent mental health, social media, and guidance and counseling services. The results indicate that BK teachers play a crucial role through individual and group counseling services, as well as prevention programs that focus on strengthening emotional management, social adjustment, and developing adaptive strategies for dealing with stress. The study also shows that the effectiveness of the BK teacher's role is influenced by school policy support, resource availability, and parental involvement. Developing mental health literacy and digital literacy in guidance and counseling services is an important strategy to improve the psychological resilience and mental well-being of adolescents in the digital era.